Bibliometric analysis of publication in human anatomy over the past ten years in Indonesia and Southeast Asia - Reza Yorghi Junianto Kartika Seputro; Dwi Cahyani Ratna Sari; Nur Arfian; Junaedy Yunus (Indonesian Journal of Biomedicine and Clinical Sciences, 2026)
Human anatomy is a fundamental basic science underpinning medical education and biomedical research. Despite a growing volume of anatomical publications, systematic evaluations of research output and thematic development among anatomy departments in Indonesia and Southeast Asian countries remain limited. With comparative insights from Southeast Asian nations, this study sought to describe the publication trends, collaboration patterns, and topic progression of anatomical research written by scholars connected to Indonesian Departments of Anatomy over the last ten years. Publications indexed in PubMed from 2016 to 2025 were used in a bibliometric study. To find literature about anatomy from Indonesia and Southeast Asia, affiliation-based search techniques were used. VOSviewer was used to map authorship collaboration, institutional contributions, and research themes based on Medical Subject Headings (MeSH) through network visualization and keyword co-occurrence studies. There were 4,067 publications from Southeast Asia and 737 publications from Indonesia. Despite making up a lesser share of regional output, Indonesia had the fastest rate of growth in publications over the research period. Productivity was concentrated among a small number of writers and institutions, according to co-authorship analysis. Keyword mapping revealed a preponderance of animal model-based experimental and preclinical research with a focus on molecular and cellular mechanisms. Cell differentiation, biomarkers, and mesenchymal stem cells were among the emerging areas associated with translational research. Anatomical research in Indonesia has expanded rapidly and is progressively integrating molecular and translational perspectives. These findings provide an evidence-based foundation for strengthening research capacity, fostering collaboration, and guiding strategic development within anatomical sciences.